2014 IEEE Conference on Control Applications (CCA) 2014
DOI: 10.1109/cca.2014.6981478
|View full text |Cite
|
Sign up to set email alerts
|

Integral line-of-sight for path following of underwater snake robots

Abstract: Abstract-This paper considers straight line path following control of underwater snake robots in the presence of constant irrotational currents. An integral line-of-sight (LOS) guidance law is proposed, which is combined with a sinusoidal gait pattern and a directional controller that steers the robot towards and along the desired path. Integral action is introduced in the guidance law to compensate for the ocean current effect. The stability of the proposed control scheme in the presence of ocean currents is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…where the detailed derivation of the matrix M p and vectors V a x , V a y , k 11 , k 12 , k 21 and k 22 is given in [11,12]. In addition, it is shown that under the influence of fluid forces (2) and torques (3), the complete equation of motion of the underwater snake robot are obtained by (4) and…”
Section: Equations Of Motionmentioning
confidence: 99%
See 4 more Smart Citations
“…where the detailed derivation of the matrix M p and vectors V a x , V a y , k 11 , k 12 , k 21 and k 22 is given in [11,12]. In addition, it is shown that under the influence of fluid forces (2) and torques (3), the complete equation of motion of the underwater snake robot are obtained by (4) and…”
Section: Equations Of Motionmentioning
confidence: 99%
“…In order to plot the Pareto frontier, one can find the solutions for different values of w p varying from 0 to 1 (and w υ changing from 1 to 0) using a small step size ∆ w p . Therefore, the optimization problem (11) can be transformed to a new optimization problem by replacing the objective function J opt to J bal in (12). In order to find the solution of the new optimization problem for specific weighting factors, an optimization algorithm is required.…”
Section: Constraintsmentioning
confidence: 99%
See 3 more Smart Citations